LINGKAR BELAJAR GURU (LBG) SEBAGAI FORUM PEMECAHAN MASALAH PGRI CABANG TLANAKAN KABUPATEN PAMEKASAN - Lailatul Musyarofah; Siti Aisyah; Asmoni Asmoni; Dwi Retnani Srinawati (STKIP PGRI Sidoarjo, 2021)
The purpose of this community service is to find out the implementation of the Teacher Learning Circle (TLC) in solving organizational problems in the Tlanakan Branch of Pamekasan Regency. Teacher Learning Circle (TLC) is a discussion forum for PGRI members at the Branch and Sub-District Levels. The method used is a focused group discussion for six meetings which begins with presentations from competent sources on the chosen topic. This activity was held at the PKG Hall, Korwilbidikbudcam, Tlanakan, Pamekasan Regency, Jl. Raya Panglegur KM 4 Tlanakan Pamekasan in November 2021. The results of this community service were in the form of recommendations related to selected topics, namely organization, employment, and the profession. The resulting recommendations were then submitted to the relevant parties who are competent in solving the problems encountered.